PENGARUH PEMBERIAN BANTUAN SISWA MISKIN TERHADAP MOTIVASI BELAJAR SISWA DI SMAN 1 BAROS TAHUN 2016 - Iba Gunawan; Kusnadi Kusnadi (FKIP, Universitas Banten Jaya, 2018)
This study was aimed to find out how the condition of student learning motivation, how the implementation of the school in supporting student learning process through financing assistance, and how the relationship between financing with student motivation in SMA N 1 Baros. Thus, the sample used was part of the population with the criteria of students receiving financing assistance, and determined using the Slovin formula. So the number of samples obtained were 121 students. Methods of data collection using questionnaires and documentation questionnaires, while data analysis methods using simple regression analysis and percentage analysis. The results showed that the students' learning motivation in good condition with the percentage acquisition of 67.76 %%. The process of giving aid in good condition with the average yield of 72.56%, and financing had a positive influence on the level of student motivation in SMA N 1 Baros that was equal to 50.5%